Teachers' sense of self-efficacy: A study of English teachers in Malaysian rural schools - Ameiruel Azwan Ab Aziz; Noraini Said; Chelster Sherralyn Jeoffrey Pudin; Kamsilawati Kamlun (Global Academic Excellence, 2021)
Teaching English as a second language (TESL) in rural schools remains a prominent issue in Malaysia. Many teachers in rural areas struggle with the seemingly insuperable difficulties associated with their underperforming rural schools in English, which is yet to be addressed significantly. This study explores ten English teachers’ sense of self-efficacy of those serving in rural schools. The lived experiences of the participants were explored through in-depth semi-structured interviews. The data gathered were analysed thematically to gain insights into the phenomenon. Three results of this study revealed the rural environmental influence aspects of teachers’ sense of self-efficacy, the context-specific nature of rural teachers’ sense of self-efficacy, and the blended philosophical concepts of social support, unswerving commitment, social obligation, and social-emotional benefits as significant driving forces to retain serving rural schools. The study’s results could contribute incrementally to the advancement of knowledge on TESL in rural schools by providing insights into the subject and context-specific descriptions.